Power factor improvement using silicon based switching devices for changing load parameters - Kumari, Popuri Rajani; Rajasri, Kasula; Reddy, Tadi Diwakara Subba; Sudhakar, Ambarapu; Rajanna, Bodapati Venkata (International Journal of Applied Power Engineering (IJAPE), 2023)
Systems power factor provides information on how effectively it uses the electrical power being provided to hold out real work. Losses rise as a results of poor power factor, and therefore the utility is penalized. In general, inductive loads, which are reactive in nature, make up AC loads. As a result, loads require and consume reactive power from the supply source which leads to excessive voltage drop in the line if they draw a lot of lagging current from the source, which could potentially result in the line's voltage collapsing if the drop is too high. When inductors cause a phase difference between voltage and current, the information is sent to the micro-controller, where the program takes control and activates the right number of opto-isolators interfaced to the triac silicon-based semiconductor device at its output to bring shunt capacitors into the load circuit to improve power factor to the desired range Semiconductors such as silicon or germanium are generally used for making triac. The most commonly used is silicon, due to its high abundance and the fact that it can operate at a higher temperature than germanium.